D’un long silence... Cicéron dans la querelle française des inversions (1667-1751) - Of a Long Silence... Cicero in the French ’Querelle des Inversions’ (1667-1751) - Lojkine, Stéphane (Ciceroniana On Line, 2020)
On the sidelines of the quarrel of the Ancients and the Moderns, the French querelles des inversions was centred on establishing whether French or Latin syntax was more closely aligned with what at the time was believed to be the natural and universal order of expression. This quarrel, which seems absurd today, played a key part in the foundation of a French grammar and of a theory of language. Throughout the debate, many an example was picked and unpicked. Among these, Cicero had a central role to play insofar as he represented the norm of the Latin language. This article seeks to explore, as part of a technical analysis, Cicero the politician as he is used in the debate around the figure of silence. The silence of the orator and the silence of the eloquent gesture are an indictment of both the rhetorical model of understanding and teaching language and the model of political expression in the public space. Cicero then embodied this dual model, as well as calling it into question.